AN ANALYSIS OF QUESTIONING TYPES OF EFL TEACHERS AT SMA AL-KHAIRAAT KOLONO - Mutmainna; Anggreni, Afrillia; Kamaruddin , Abdul (e-Journal of ELTS (English Language Teaching Society), 2024)
The objective of this research is to find out the types of questions used by the classroom teachers of the second-grade students at SMA Al-KhairaatKolono. The research used qualitative description method. The data were obtained from observation and interviews. The subjects of this research were two English teachers at SMA Al-KhairaatKolono. The results of this research showed that English teachers used three types of questions the teaching and learning process, namely Knowledge, Comprehension, and Evaluation. However, the second teacher did not use the Evaluation types of questions. Furthermore, from the results of interview, the purposes of the teachers used these types of questions are, first to measure the students’ understanding. Second, help the teacher in training the students to improve their skill in giving opinions. Third, it was simple and easy for the students to understand the material. From using the questioning strategy, there are several implications including increasing students’ activity during the teaching and learning process, Students are also able to involve themselves in answering questions from the teacher and able to understand the material provided by the teachers.